A case of late diagnosis of a foreign body in bronchus in a child - O.O. Rechkina; O.M. Kravtsova; N.V. Promska; M.S. Opanasenko; O.V. Tereshkovych; O.I. Shpak; L.I. Levanda (Zaslavsky O.Yu., 2020)
Respiratory foreign bodies are a fairly common and dangerous problem in pediatrics. According to the literature, 70 % of all cases are foreign bodies of the bronchi, most often in the right (up to 80 %). Diagnosis is based mainly on anamnestic data and clinical manifestations characteristic of a particular type of obstruction. X-ray examinations are performed in all cases of suspicion of a foreign body, but they are X-ray contrast in no more than 20 % of cases. That is if the fact of aspiration was forgotten or unnoticed, the diagnosis is difficult, especially with foreign bodies in small bronchi, which for a long time do not manifest themselves. Clinical signs already appear when chronic inflammation with a purulent process develops in this place, which leads to the complications - bronchiectasis, fibrosis, or pulmonary hemorrhage. At the same time treatment is often only operative. For clarity, we present a clinical case of late diagnosis of a small bronchial foreign body in an adolescent child. Its features are as follows: lack of anamnestic data on aspiration, relatively adult age of the child, X-ray non-contrast of a foreign body, atypical placement, preserved lung ventilation in the damaged area. This case once again emphasizes the need for vigilance of pediatricians regarding this pathology in children of any age. The only reliable method of early diagnosis of airway foreign bodies is tracheobronchoscopy.